If a×cos x + b × cos x = c, then the value of (a × sin x – b²cos x)² is

  • a)
    a² + b² + c²

  • b)
    a² - b² - c²

  • c)
    a² - b² + c²

  • d)
    a² + b² - c²

Correct answer is option 'D'. Can you explain this answer?

Related Test

Answers

Mohit Rajpoot
May 07, 2021
(a×cos x + b × sin x)² + (a × sin x – b × cos x)² = a² + b²
⇒ c² + (a × sin x – b × cos x)² = a² + b²
⇒ (a × sin x – b × cos x)² = a² + b² – c²

(a×cos x + b × sin x)² + (a × sin x – b × cos x)² = a² + b²⇒ c² + (a × sin x – b × cos x)² = a² + b²⇒ (a × sin x – b × cos x)² = a² + b² – c²

Download free EduRev App

Track your progress, build streaks, highlight & save important lessons and more!
(a×cos x + b × sin x)² + (a × sin x – b × cos x)² = a² + b²⇒ c² + (a × sin x – b × cos x)² = a² + b²⇒ (a × sin x – b × cos x)² = a² + b² – c²